The Effect Of The Quizizz Assisted Paikem Approach On Student's Motivation In Mathematics Learning - Shevia Annisa; Maman Fathurrohman (Jurusan Pendidikan Matematika FKIP Universitas Halu Oleo, 2023)
A rigid and less varied learning approach is one of the causes of low student motivation in learning mathematics. This situation will indirectly have an impact on the low achievement of learning objectives and student learning outcomes of mathematics. The purpose of this research is to determine the effect of the Quizizz-assisted PAIKEM approach on students' learning motivation in learning mathematics. This research includes quantitative research whose research method is a quasi-experimental design with Non-Equivalent Control Group Design. The population in this study were all eighth-grade students at SMPN 1 Kragilan, while the samples were experimental and control classes with 34 students each. The data collection technique in this research uses a non-test instrument in the form of a learning motivation questionnaire which will be given in the form of a pretest and posttest. Analysis of research data using descriptive and inferential statistical analysis. Descriptive statistical analysis was carried out to describe the research and to obtain descriptive data such as the mean, minimum and maximum scores, standard deviation, variance and range. Meanwhile, inferential statistics will test the research hypothesis by using the independent sample t-test. The results of the t-test analysis showed that there was a significant difference between the group of students whose learning was carried out using the Quizizz-assisted PAIKEM approach and the group of students whose learning was carried out using the conventional learning approach.